Can povidone iodine gargle/mouthrinse inactivate SARS-CoV-2 and decrease the risk of nosocomial and community transmission during the COVID-19 pandemic? An evidence-based update. (November 2021) - Chopra, Aditi; Sivaraman, Karthik; Radhakrishnan, Raghu; Balakrishnan, Dhanasekar; Narayana, Aparna
Abstract: The Coronavirus disease in 2019 (COVID-19), also referred to as the novel 'CoV19 (nCov19)' is caused by a new coronavirus strain similar to Severe Acute Respiratory Syndrome (SARS-CoV-2). SARS-CoV-2 spreads via respiratory droplets, saliva, or direct contact. Therefore it is important to control the viral load in the saliva and respiratory secretions. One of the most simple and cost-effective measures that can be adopted by the public and healthcare professionals to prevent cross-contamination and community transmission, is the implementation of effective oral and throat hygiene. Recent evidence has confirmed that 0.5% povidone iodine (PVP-I) mouthrinse/gargle for 30 s can reduce SARS-CoV-2 virus infectivity to below detectable levels. PVP-I can even interrupt SARS-CoV-2 attachment to oral and nasopharyngeal tissues and lower the viral particles in the saliva and respiratory droplets. Thus, the use of PVP-I mouthrinse as a prophylactic measure has been advocated across the globe to reduce disease transmission. Although the efficacy of PVP-I against SARS-CoV-2 is proven, no review articles have yet discussed the evidence and mechanisms of PVP-I against the SARS-CoV-2. Thus, this paper highlights the rationale, safety, recommendations, and dosage of PVP-I gargle/mouthrinse as an effective method to decrease the viral loads during the pressing times of COVID-19.